The Effects of Skimming and Scanning in Reading Comprehension of the Pre-University Students of the Ielts Preparation Class in Sun Education Batam - Harnila Harnila (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
This research is aimed at investigating the effects of Skimming and Scanning Techniques on the reading comprehension of the pre-university students of the IELTS Preparation Class in SUN Education Batam. This research was a pre-experimental research. The researcher took the pre-university students of the IELTS Preparation Class in SUN Education in academic year 2018 as the subject of the study. The data was collected by documenting, observing, and interviewing. The result of data analysis showed that the implementation of the scanning and skimming techniques can improve students’ reading comprehension. It was found that from the mean result scores of the post-test, the students’ reading band score escalated gradually. During the learning process, the students were stimulated to apply skimming and scanning as their reading techniques. There were nine steps in implementing of the scanning and skimming technique in teaching reading; (1) to read the passage and look at the title; (2) to find key words; (3) to read the first sentence of every paragraph completely; (4) to identify main ideas of a certain paragraph; (5) to read the final paragraph completely; (6) to predict the meaning (8) to focus on the details; (9) to find out implicit information of the reading text.